Qualidade dos parques de vizinhança e parques de bairro: uma proposta de índices de avaliação - Rodrigues, Gabrielle de Melo (2012)
This study aims to evaluate the quality of vicinity parks and neighborhood parks by obtaining qualitative indices, enabling diagnostics that can support planning activities. Assuming that the terms of vicinity parks and neighborhood parks belongs to the system of free and green areas within the urban structure and the lack of a qualitative evaluation difficults research and analysis of such spaces, we sought to define the indicators of quality required for the composition of technical evaluation methodology. Particularized to the ecological functions, urbanistic, aesthetic, social and of leisure, the choice of qualitative attributes in theoretical references of various authors that regards the qualitative importance of cited elements was based on the evaluation methodology, as well as in the participation of specialists in the urban themes, which helped in the development and definition by completing a questionnaire where they could evaluate the elements that are considered essential in the composition of the vicinity and neighborhood parks. The object of study are the vicinity parks and neighborhood parks in view of its relative standardization or programmatic similarity. Thus, will be presented as indices of quality, the results obtained by applying this methodology. The landscape unit chosen for application of the methodology were the neighborhoods Torre and Madalena, in Recife, Pernambuco, Brazil, at 2011. The survey sample was first defined by the relationship that each Recife's political-administrative region (PAR) has with the number of parks in total area (m²). Being the PAR 04 the political-administrative region that has the highest concentration of parks in square meters, were selected by raffle, two neighborhoods located in this PAR. The definition of the basic units of study was considered from the function as recreation and social interaction support and the following criteria: location and dimensions, resulting in the selection of a vicinity park at Madalena's neighborhood and a neighborhood park at Torre. Thus, the adoption of this methodology for evaluate the quality of vicinity parks and neighborhood parks, would test the degree of universality and appropriateness of the parameters of the assessments. The results showed that the quality levels obtained by applying the methodology of technical qualitative evaluation were consistent with the perception of quality assigned by the community. It was found that the indicators system of the quality index of vicinity park and quality index of neighborhood park showed to be adequate and consistent for measuring the qualitative aspects, particularized to the ecological functions, urbanistic, aesthetic, social and of leisure, thus giving valid subsidies for urban and environmental planning.